Possibilities of voltammetric determination of pyridine herbicide picloram using boron-doped diamond electrodes - Bandžuchová, Lenka; Švorc, Ľubomír; Vojs, Marian; Marton, Marián; Michniak, Pavol; Chýlková, Jaromíra (Univerzita Pardubice, 2014)
Voltammetric behavior of a wide-spread used pyridine herbicide picloram (PCR) was investigated using two different types of boron-doped diamond working electrodes: commercial available and self-assembled. PCR provided one irreversible oxidation peak in an acidic medium occurring at very positive potential (about +1.5 V vs. Ag/AgCl/ 3 mol L−1 KCl) in both cases. 1 mol L−1 sulfuric acid was selected as the most suitable supporting electrolyte for electrochemical oxidation of PCR. Differential pulse voltammetric methodology was elaborated and its operating parameters were optimized to achieve the best analytical performance for determination of PCR. Both working electrodes provided high repeatability, wide linear concentration range and low limit of detection. Applicability of proposed method was verified by analysis of PCR in model samples of tap and natural waters and human urine, respectively.
Keywords: picloram; boron-doped diamond electrode; voltammetry; determination